Efficiency Of Trawl Cod End For Catching Result In Lambur Luar East Muara Sabak East Tanjung Jabung Jambi Province - Sri Jarwanto; Isnaniah '; Irwandy Syofyan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted at December 2013 in the Lambur Luar, East Muara Sabak, East Tanjung Jabung, Jambi Province. The purpose of this study was to determine the efficiency of Trawl cod end. While the benefits are expected to provide useful information for writers, for readers, and for the people Lambur Luar, as well as an input to the fisher of Lambur Luar to modify fishing gear and Trawl cod end size so as to correspond to the number of catches expected. Efficiency of Trawl cod end is a principle which enables the achievement of the best comparison between total catches and volume of Trawl cod end. Efficiency values of Trawl cod end obtained from the division between total catches per operation with Trawl cod end volume and multiplied by 100 %. The trawl cod end of Lambur Luar is very inefficient, it can see from the result the values of trawl cod end efficency between 0,1-0,31. The average of trawl cod end efficiency is 0,15.Keywords : Efficiency, Trawl cod end, Total catches.